EFEKTIVITAS METODE BERCERITA TERHADAP KEMAMPUAN PENINGKATAN KOSAKATA PADA ANAK DOWN SYNDROME DI SURAKARTA : THE EFFECTIVITY OF THE STORYTELLING METHOD IN IMPROVING THE VOCABULARY OF CHILDREN WITH DOWN SYNDROME IN SURAKARTA - Martiza Tri Wirdayanti; Windiarti Dwi Purnaningrum; Putri, Anggi resina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Down's syndrome is a chromosomal abnormality of the 21st chromosome pair that affects hundreds of genes, including those coding for amyloid proteins in the brain. This protein can trigger the activation of microglia, which damage nerve cells. Children with Down's syndrome often have speech delays and language development that is not age-appropriate and does not match their intelligence. Vocabulary enrichment is very important for children with Down's syndrome, as they tend to have a limited vocabulary and difficulty understanding and using new words. By expanding their vocabulary, these children can more easily understand the relationship between words and their meanings, which will help them communicate more effectively and improve their general cognitive abilities. In this study, the Northwestern Syntax Screening Test developed by Laura L. Lee and adapted by Rozella J. Sutasdisastra, M.S., CCC-LP was used. .